Racial differences in veterans' response to a standard vs. patient-centered decision aid for prostate cancer: Implications for decision making in African American and White men. Issue 12 (December 2020) - Langford, Aisha T.; Scherer, Laura D.; Ubel, Peter A.; Holmes-Rovner, Margaret; Scherr, Karen A.; Fagerlin, Angela
Highlights: A secondary analysis of a study of men diagnosed with early stage prostate cancer. Racial differences in response to two different decision aids (DA) were evaluated. White patients who received the patient-centered DA preferred active surveillance. African American patients' treatment preferences did not differ as a function of DA. Abstract: Objective: To determine whether racial differences exist in patient preferences for prostate cancer treatment after being informed about options using a patient-centered vs. a standard decision aid (DA). Methods: This article reports secondary analyses of a large study of men diagnosed with early stage prostate cancer. Men were recruited from 4 VA Health Systems and randomized to receive a patient-centered or standard DA about prostate cancer treatment options. Data were collected at 1) baseline, 2) after reading the DA but prior to diagnosis, and 3) after receiving a cancer diagnosis and meeting with a urologist. Results: White patients who received the patient-centered DA written at a 7 th grade reading level were more likely to prefer active surveillance and less likely to prefer radiation compared to those who received the standard DA written at >9th grade reading level. African American patients' treatment preferences did not differ as a function of DA. Conclusions: When informed about prostate cancer treatment options through a patient-centered DA, White patients changed their treatment preferences but African American patients did not. Practice Implications: As DAs are increasingly being used in clinical practice, more research is needed regarding the efficacy, relevance, and receptivity of DAs for African Americans.